Prefrontal-hippocampal pathways underlying adolescent resilience. - Wei, Luqing; Wu, Zhengdong; Xia, Qi; Baeken, Chris; Wu, Guo-Rong (European Child & Adolescent Psychiatry, 2025)
The prefrontal-hippocampal pathways are integral to memory suppression, facilitating positive and adaptative responses following traumatic events. However, the role of these circuits in promoting resilience among adolescents remains largely unknown. This study used structural similarity analysis of MRI-based gray matter volume (GMV) to map connectivity networks centered on the hippocampus, investigating whether structural similarity between prefrontal regions and hippocampus were related to resilience in a cohort of 145 adolescents. Additionally, spatial correlation analyses of resilience-related structural similarity network and neurotransmitter distribution maps were conducted to identify molecular adaptations within prefrontal-hippocampal circuits associated with resilience. The results showed that higher resilience levels were correlated with stronger structural similarity between the prefrontal areas (i.e., middle frontal gyrus and orbitofrontal cortex) and hippocampus. Furthermore, the serotonergic neurotransmitter system, which modulates neural oscillations in prefrontal-hippocampal pathways, appears to be associated with resilience. The current findings suggest that structural and molecular adaptations within prefrontal-hippocampal circuits, which are implicated in the suppression of intrusive, unwanted memories, may foster resilience in young people. These insights advance our knowledge of the neurobiological markers of resilience, paving the way for more targeted and effective therapeutic interventions to bolster resilience and mitigate adverse outcomes in developmental populations.